Cyclic oligomers of oxetane-based dipeptide isosteres derived from L-rhamnose - Fleet, G; Johnson, S; Jones, J (2006)
Two new cyclic oligomers, cyclo-tetra-[2,4-anhydro-3-O-tert- butyldimethylsilyl-5-deoxy-L-rhamnonamido-(N→5)] and the corresponding 6-deoxy-D-gulonate cyclic 'tetramer', have been synthesised from linear tetrameric oligomers, using TBTU- and pentafluorophenyl ester-based methodologies, respectively. These two compounds constitute a novel class of cyclic oligomers derived from oxetane-based sugar amino acids. Copyright © 2006 European Peptide Society and John Wiley and Sons, Ltd.